2013
DOI: 10.1107/s1600536813031395
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl 3-(10-bromoanthracen-9-yl)-5-methyl-1,2-oxazole-4-carboxylate

Abstract: Key indicators: single-crystal X-ray study; T = 100 K; mean (C-C) = 0.002 Å; R factor = 0.025; wR factor = 0.074; data-to-parameter ratio = 18.1.In the title compound, C 21 H 16 BrNO 3 , the mean planes of the anthracene tricycle and isoxazole ring are inclined to each other at a dihedral angle of 72.12 (7) . The carboxy group is slightly out of the isoxazole mean plane, with a maximum deviation of 0.070 (5) Å for the carbonyl O atom. In the crystal, pairs of weak C-HÁ Á ÁO hydrogen bonds link the molecules in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…This stereoelectronic effect was also previously observed in our crystallographic studies of isoxazole-3-anthracenes 9,1317 and isoxazole-3-anthroquinones. 18 The isoxazole and ester are largely co-planar with the dihedral angle between the isoxazole mean plane and plane containing the ester carbonyl and ether atom being 10.89°.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…This stereoelectronic effect was also previously observed in our crystallographic studies of isoxazole-3-anthracenes 9,1317 and isoxazole-3-anthroquinones. 18 The isoxazole and ester are largely co-planar with the dihedral angle between the isoxazole mean plane and plane containing the ester carbonyl and ether atom being 10.89°.…”
supporting
confidence: 86%
“…30,31 In the current case it should be recalled that the AIMs are distinguished in every crystal structure and computation to date by a dihedral angle of 74–880° between the mean planes of the isoxazole to the anthracenyl moiety. 6,1317 This conformation would be expected to have lower surface area and hence lower lipophilicity than an alternative conformation which is planar and conjugated. These properties may improve bioavailability and allow the AIMs to permeate cell membranes as well as the blood brain barrier.…”
mentioning
confidence: 99%
“…ISSN 2056-9890 The bicyclic acetal (BA) I can be formed directly via a Criegee-like rearrangement through intermediate IV, or alternatively stepwise via the intermediacy of one electron reorganization to an intermediate diepoxide V (Filatov et al, 2017). Of the ten previous crystal structures of anthryl isoxazoles published by our group (Mosher et al, 1996;Han et al, 2002Han et al, , 2003Li et al, 2006Li et al, , 2008Li et al, 2013;Duncan et al, 2014;Weaver et al, 2015), and the three N-heterocyclic structures solved and disclosed (Weaver et al, 2020), this is the first example we have observed of this rearrangement. Given the observation of this rearrangement it is advisable that the o-pyridyl AIM (II) be stored under an argon atmosphere at low temperature (233 K or below).…”
Section: Chemical Contextmentioning
confidence: 68%
“…Preparation and molecular structures of the title compounds. tion (Weaver, Stump et al, 2020;Weaver et al, 2015;Li et al, 2013;Li et al, 2006;Han et al, 2003;Mosher et al, 1996).…”
Section: Figurementioning
confidence: 99%